Socio-Economic Life in the Surkhan Oasis at the End of the 19th Century - The Beginning of the 20th Century - Faizulla Tilovov (Zien Journals, 2023)
This article talks about handicraft products necessary for the daily life of residents of the Surkhan oasis in the beginning of the 19th-20th centuries, goods produced by the residents, types of handicrafts formed in the oasis from the early Iron Age to the present day
Keywords: Termiz; Chaganiyan; Darzangi; blacksmithing